L-Asparaginase potential in acrylamide mitigation from foodstuff: a mini-review - Munir, Naveed; Zia, Muhammad Anjum; Sharif, Sumaira; Tahir, Imtiaz Mahmood; Jahangeer, Muhammad; Javed, Irum; Riaz, Muhammad; Sarwar, Muhammad Usman; Akram, Muhammad; Shah, Syed Muhammad Ali (Progress in Nutrition, 2019)
L-Asparaginase (E.C. 3.5.1.1, LA) also known as L-asparagine amidohydrolase, specifically catalysis the breakdown of amino acid asparagine to aspartic acid and ammonia. It reduces the level of acrylamide that is produced during the baking of starchy foods. L-Asparaginase is widely distributed in animals, plants, and microorganisms. In food industries, acrylamide synthesized during the process of baking and frying at high temperatures under low moisture content during Maillard reaction, a non-enzymatic reaction. As acrylamide is a potential carcinogen, so strategies for its mitigation have significant importance on its level in the final product. Asparagine acts as a precursor in the process of acrylamide synthesis, so utilization of L-Asparaginase reduced its concentration in the final product. In this review, we have discussed the various pathways of acrylamide synthesis as well as different strategies for its elimination from final food products.